Culture Insight Of New Age Technology For Underdeveloped Society Lidia Djuhardi Faculty of Communication Science - Lidia Djuhardi (Yayasan Ilomata, 2021)
This study entitled “Culture Insight Of New Age Technologies For Underdeveloped Society “,is about underdeveloped society in Temajuk Village, Indonesia-Malaysia border area, where is still underdeveloped area. This study aimed to find out the insight of new age technologies from Temajuk villager through their experiences about new technology and their meanings. In addition, the approach of this study is using qualitative-descriptive with interpretive paradigm through fenomenologi studi. The subject of this study is the villager who lived in Temajuk Village, located in the end of Borneo Island that directly borders with Malaysia. The subject is selected purposively, based on the context and the need of research. The data collection was conducted through interview, observation, literary review and documentations. The result for the culture insight of Temajuk society about new technologies are,the experiences more dynamic and its meanings independence life for them. The insight conclusion is the are very anthusiasm for the new technolog , its influenced by the history and conditions that build a culture insight for society of Temajuk village. Keywords: New Age Technology ; Smartphones; Culture Insight ;Temajuk Village; Underdeveloped Society